Interdisciplinary students’ reflections on the development of their epistemic fluency - van Goch, Merel Margot (Frontiers in Education, 2023)
How can higher education institutions foster students’ epistemic fluency, that is, their ability to identify, reflect upon, and connect different knowledges and different ways of knowing? As higher education institutions put interdisciplinary research and education prominently on their strategic agendas, there is a call for knowledge on how to teach students to identify and integrate insights from different disciplines. This study approaches this topic from the viewpoint of the student: what are the drivers and barriers to the development of epistemic fluency, according to interdisciplinary students? Participants were undergraduate students enrolled in a course on the interdisciplinary research process with a specific emphasis on integration. In the first and last lectures of the course, students were asked to reflect on their openness to alternative perspectives and their connective thinking. They also reflected on their development in general and specifically in this interdisciplinary course. Students were able to meaningfully reflect on their development and the results showed a varied picture of students’ epistemic fluency.